The Effect of Cued Speech on Language Skills (Topic Maintenance, Basic Information and Sequence Events of the Story) in Late Implanted Pre-Lingual Hearing Impaired Students: The Benefits of Persian Cued Speech - Shokoufeh Mirza-Aghabeigi; Gita Movallali; Mohammad Taheri; Salimeh Ja'fari (University of Social Welfare and Rehabilitation Sciences, 2015)
Objective: Cochlear Implant has very positive impact on expressive language growth of children with severe impaired hearing and the effectiveness of Cued Speech has been studied in several investigations. The purpose of this study was to assess the effectiveness of using Cued Speech on topic maintenance, basic information and sequence events of the story in the late cochlear implanted prelingually hearing impaired students. Materials & Methods: This has been an experimental study and pre-test, post- test plan was used. Nine prelingually hearing impaired students who were late cochlear implanted and were between the ages of 11 and 16 years and 9 months from Loghman Cochlear implant center were selected by available sampling method. Our tool was story telling test. The Persian Cued Speech training program was carried out for 8 weeks in sixteen 60-minutes sessions. After that all students were assessed again. In this study we have used Kolmogorov - Smirnov Z-test and t-test for dependent groups. Results: Results revealed Cued Speech have positive and significant effects on topic maintenance, basic information and sequence events of the story in the late cochlear implanted pre-lingually hearing impaired students (P&le0.01). Conclusion: Our results demonstrated that using Cued Speech for the late cochlear implanted pre-lingually hearing impaired students can be effective for their language skills.